The Effect of Intravenous Vitamin C on Urine Neutrophil Gelatinase-Associated Lipocalin Among Septic Patients: A Randomised Control Trial - Peni Yulia Nastiti; Adhrie Sugiharto; Amir S Madjid (HM Publisher, 2019)
Background The role of vitamin C to decrease organ dysfunction in sepsis was still controversial. This study aimed to explore the effect of intravenous (IV) vitamin C on urine NGAL (uNGAL) levels among septic patients in ICU. Methods This study was a randomized clinical trial held in Cipto Mangunkusumo Hospital from April to July 2019 with consecutive sampling method. Patients aged > 18 years with sepsis based on the criteria of sepsis-3 who were admitted to the ICU were included in this study. Exclusion criteria were those with chronic kidney problems, with kidney stones, undergo renal replacement therapy in the ICU. All subjects were divided into: Group A was treated with combination of vitamin C and thiamine while Group B was given thiamine only. The uNGAL level was measured at baseline, 24, 48 and 72 h after treatment. Anova for repeated measurement using General Linear Model for Repeated Measurement was used with level of significant at p-value <0.05. Results Total of 33 subjects were included. In Group A we found uNGAL (ng/ mL) were 74.5 (13.3-102.9), 77.3 (15.2-98.4), 67.2 (22.6-100.6), 77.2 (17.0-100.5) for baseline, 24 h, 48 h, and 72 h respectively. While in Group B uNGAL were 57.7 (11.5-94.5), 57.1 (6.4-97.7), 53.7 (13.3-99.6), 47.6 (4.5-100.9). No significant difference in terms of uNGAL between two groups at each hour was found. Conclusions This study showed that intravenous vitamin C administration had no effect on uNGAL among septic patients. Need more study to investigate approaches to improve kidney and inflammatory biomarker among septic patients.